Role of Journalists during COVID 19 Pandemic in Nepal - KC, Poshan Raj (International Journal of Social Sciences and Management, 2025)
This research focuses on the contributions of Nepalese journalists during crisis with especial focus on the COVID-19 pandemic in Nepal. Employing survey and interview data analysis methods, the study investigates their personal, social, and professional experiences. The study involves data analysis in two phases. In the preliminary phase, it designs a survey form and sends to most of the journalists in Nepal and collects the responses of the first 125 journalist’s data. It analyses those data and interprets using tabular methods and interpretive methods. In the second phase, it selects journalists for further investigations. In order to avoid biases, two journalists (one male and one female) have been selected from each provinces of Nepal for personal or telephone interviews. All the confusions of the first phase analysis have been further inquired in this discussion phase. Moreover, the study includes a separate ‘discussion’ topic and incorporated their point of views. Finding shows that throughout the pandemic, media houses faced heightened vulnerability, leading to complete or partial closures. Many respondents reported salary reductions, highlighting the lack of commitment from media houses to employee well-being. This also underscores the inadequate market research, social responsibility, diversified income streams, and crisis preparedness among most media outlets. Furthermore, the study identifies a plethora of related topics warranting future investigation. Subsequent research could explore diverse geographical and cultural contexts in which journalists navigated the pandemic. This includes an examination of their experiences across print, electronic, and digital media platforms. Int. J. Soc. Sc. Manage. Vol. 12, Issue-1: 27-37.